Phenomenal intentionality - Kriegel, Uriah (Philosophy of mind series., 2013)
Phenomenal intentionality is supposed to be a kind of directedness of the mind onto the world that is grounded in the conscious feel of mental life. This book of essays explores a number of issues raised by the notion of phenomenal intentionality.